An EPR study of point defects in zinc oxide thin films - Heydari, Jinan Fadel Mohammad Ali; Yukselici, Mehmet Hikmet (IOP Publishing Ltd, 2024)
We studied ZnO thin films deposited on glass slides by thermal evaporation in vacuum followed by heat treatment in open air or Ar flow. The samples were characterized using x-ray diffraction, Raman scattering, photoluminescence (PL), and electron paramagnetic resonance (EPR) spectroscopy. We observed a broad PL band in the visible region at spectral positions of 504 and 560 nm and a low-intensity band in the UV region at 390 nm. The EPR spectra display a clear first derivative structure at g=1.96 at temperatures below 200 K. The PL spectrum shows red-shifted valence to conduction band emission due to electron hole recombination through shallow surface states. We found an activation energy of E a = 4.2 meV using the Arrhenius plot and estimated concentrations of paramagnetic defects and spin-spin relaxation time constants of 1016 m-3 and 10-14 s, respectively.
Keywords: EPR; defects; zinc oxide; thin films; point defects; OXYGEN VACANCIES; ZNO; PHOTOLUMINESCENCE; MECHANISMS; Materials Science